Lupus with myositis in an adult Indian male - Narula, Shubhank; Kakar, Atul; Batra, Tanvi (International Journal of Research in Orthopaedics, 2024)
Systemic lupus erythematosus (SLE) is a chronic inflammatory disease that involves various organs and has a vast spectrum of multi system involvement. SLE is an autoimmune illness which is rarely found in males but when present holds a poor prognosis with a predisposition to develop various manifestations. This case involves a 50-year-old male who developed myositis as a complication of lupus despite adequate immunosuppressive therapy.